Hybridization using promising second generation inbred and molecular characterization of a the third generation inbreds of WCT coconut - Hassain, N (Department of Plant Breeding and Genetics College of Agriculture, 2018)
The research project entitled “Hybridization using promising second generation inbred and molecular characterization of the third generation inbreds of WCT coconut (Cocos nucifera L.)” was carried out in the Department of Plant Breeding & Genetics, College of Agriculture, Padannakkad during the year 2016-2018. The major objectives of this study include development of D x T hybrids using promising palms in second generation (S2) inbreds of West Coast Tall (WCT) as male parent and Malayan Yellow Dwarf (MYD) as female parent and characterization of third generation (S3) inbred seedlings of superior S2 palms of WCT using RAPD analysis. For hybridisation, the male parent was selected from the superior inbred family based on the reports on morphological evaluation and estimation of inbreeding depression during the period 2013-2015 (Chethana, 2016). The family IIIS2-1 showed lowest inbreeding depression for yield related traits among 12 families followed by VS2-2. The palm 313 (IIIS2-1) and 225 (VS2-2) were selected as male parents. Superior MYD palm to be used as the female parent was selected from among the MYD palms available at CoA, Padannakkad based on the general features of mother palm selection (Nair et al., 2008). Observations were recorded from these parental palms which included 24 morphological characters. The male parents showed inbreeding depression for several vegetative characters such as stem girth, functional leaves etc and reproductive characters such as number of female flowers per inflorescence, setting percent and nut yield per palm per year, compared to WCT. The results showed that inbreeding depression for these characters was more in palm 313 (developed by selfing) than palm 225 (developed by sibmating). Total five nuts were harvested from MYD (two nuts by using pollen from palm 313 and three nuts using pollen from palm 225) during May 2018 and were sown in the nursery. Molecular characterization of the 15nos of S3 inbred seedlings of IIIS2 family planted in the field in replicated plots were done using RAPD. Genomic DNA was isolated from 15 seedlings of IIIS3 family among which 10 were produced by selfing the S2 palms (IIIS3-1) and 5 were produced by sibmating the S2 palms (IIIS3-2) along with COD, CGD and WCT. After DNA isolation, samples were subjected to RAPD analysis using 10 decamer primers namely OPAU02, OPBA3, OPAW14, OPAW19, OPAW12, OPAW13, OPAW13, OPAW09, OPAU03, OPAW08 and OPAW15 selected based on screening 30 primers. Using primer OPAW08, a band of size of ~400bp was specifically found in inbreds alone while it was absent in dwarfs and WCT seedlings. In OPAU 03 primer, band size of ~1200bp was absent in WCT but present in all inbreds and CGD. The sibmated inbred NL1 showed a distict pattern when amplified with OPAW 09 compared to all other inbreds. The primer produced a specific band of size ~1050bp only in the sibmated inbred CL1 and was absent in all other samples. Amplification with OPAW19 primer produced a banding pattern in which it mainly distinguished CGD from all other seedlings where there were only two bands while others were having six bands. Primer OPAU 02 produced two unique amplicons: 1100bp present in selfed inbred I1M1 TH2 and MYD; 1000bp present in COD and MYD. Genetic similarity among the 15 IIIS3 seedlings, CGD, COD, MYD and WCT was estimated by using of software DARwin (Darwin 6.Ink). The dendrogram indicated three major clusters in which the grouping of several inbreds along with WCT, COD and CGD may be an indication supporting the hypothesis that the dwarfs might have been originated from the talls during the course of evolution followed by selection. The two dwarfs present in the group are COD and CGD which are from Chavakkad area in Kerala and WCT is the most common cultivar of Kerala. As a future line of study, further evaluation of these S3 inbreds regarding the flowering time and yield characters has to be carried out to find out the genetic potential of these inbreds as breeding lines for producing superior hybrids. The seedlings to be emerged from the hybrid nuts produced in the present study, though limited in number, needs to be evaluated for important traits and the hybridisation programme using superior palms in S2 generation needs to be continued for production of more number of hybrid nuts.